ANALISIS PENERAPAN METODE E-PURCHASING PADA PENGADAAN BARANG DAN JASA - Siti Nur Saidah; Sekar Suci Ningtyas; Pitri Puspita Sari; Sigit Djalu Purwoko (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstrak. Negotiating prices before purchasing is one of the steps in carrying out procurement activities which have the aim of obtaining goods and services needed to meet the needs of groups of government and private entities, such as ministries, institutions, regional apparatus and other government institutions. This research aims to thoroughly describe the method of implementing E-Purchasing in the process of procuring goods and services. The research method used is a literature review approach in which this research analyzes a number of academic studies, articles and books related to electronic purchasing activities (E-Purchasing) in the process of purchasing goods or services. The focus of this research includes the application of the E-purchasing Method to procurement of goods and services electronically or using a system. The results of this research underline that e-purchasing is not only an efficiency tool, but also a strategy that involves legal aspects, risk management and negotiations to ensure success in the procurement of goods and services at the government or private level. Keywords: Methods; Procurement of Goods and Services; E-Purchasing System.